CXCL16/CXCR6-mediated adhesion of human peripheral blood mononuclear cells to inflamed endothelium. (October 2019) - Linke, Bona; Meyer Dos Santos, Sascha; Picard-Willems, Bettina; Keese, Michael; Harder, Sebastian; Geisslinger, Gerd; Scholich, Klaus
Highlights: Platelet/CD68 + cell-clusters in atherosclerotic lesions express CXCL16 and CXCR6. CXCL16 + peripheral blood mononuclear cells adhere to CXCR6 + platelets under flow. CXCL16 on inflamed HUVECs promotes the firm adhesion of CXCR6 + PBMCs under flow. Abstract: The endothelial chemokine CXC motif ligand 16 (CXCL16) is involved in the recruitment and firm adhesion of CXCR6 + cells to the atherosclerosis-prone aortic vessel wall. Recently we showed that CXCR6 + platelets from flowing blood attach to CXCL16 expressed by activated endothelium on the luminal side of the blood vessel. With this study we supplement these findings with the observation that platelets bound to the inflamed endothelium are presenting CXCR6 to CXCL16-positive peripheral blood mononuclear cells (PBMCs) and, thus, are mediating an increased adhesion of PBMCs to the arterial wall. Furthermore we identified endothelial CXCL16 as an important adhesion molecule promoting the firm adhesion of CXCR6-positive PBMCs to inflamed endothelium. Our results demonstrate that endothelial CXCL16 as well as platelet CXCR6 are acting as potent PBMC-adhesion ligands, inducing PBMC-adhesion to the atherosclerosis-prone vessel wall and thus promoting the progression of atherosclerosis.